Dronabinol increases pain threshold in patients with functional chest pain: a pilot double-blind placebo-controlled trial. Issue 2 (20th December 2016) - Malik, Z.; Bayman, L.; Valestin, J.; Rizvi-Toner, A.; Hashmi, S.; Schey, R.
SUMMARY: Noncardiac chest pain is associated with poor quality of life and high care expenditure. The majority of noncardiac chest pain is either gastresophageal reflux disease related or due to esophageal motility disorders, and the rest are considered functional chest pain (FCP) due to central and peripheral hypersensitivity. Current treatment of FCP improves 40–50% of patients. Cannabinoid receptors 1 (CB1 ) and 2 (CB2 ) modulate release of neurotransmitters; CB1 is located in the esophageal epithelium and reduces excitatory enteric transmission and potentially could reduce esophageal hypersensitivity. We performed a prospective study to evaluate its effects on pain threshold, frequency, and intensity in FCP. Subjects with FCP received dronabinol (5 mg, twice daily; n = 7; average age, 44 years; mean body mass index, 26.7) or placebo ( n = 6; average age, 42 years; mean body mass index, 25.9) for 28 days (4 weeks). Chest pain, general health, and anxiety/depression questionnaires were assessed at baseline and at 4 weeks. Subjects underwent an esophageal balloon distention test prior to treatment and on last day of the study. Dronabinol increased pain thresholds significantly (3.0 vs. 1.0; P = 0.03) and reduced pain intensity and odynophagia compared to placebo (0.18 vs. 0.01 and 0.12 vs. 0.01, respectively, P = 0.04). Depression and anxiety scores did not differ between the groups at baseline or after treatment. No significant adverse effects were observed. In this novel study, dronabinol increased pain threshold and reduced frequency and intensity of pain in FCP. Further, large scale studies are needed to substantiate these findings.